Where winners live sell more, earn more, achieve more through personal accountability - Porter, Dave 1961- (Jossey-Bass, Wiley, 2013)
Be accountable and achieve success Personal accountability is the secret weapon of every successful sales professional. It is the secret weapon of Where Winners Live co-author Dave Porter, who became the owner and CEO of Baystate Financial Services at age 35 and grew it into a 100 million-a-year business over the next 15 years. It is the secret weapon of Where Winners Live co-author Linda Galindo, who transformed herself from the self-proclaimed Queen of Victims into an entrepreneur, business coach, consultant and speaker whose typical audience numbers 500 or more. Like all.